Coupled Effect of Electronic Medical Record Modifications and Lean Six Sigma Methodology on Rheumatoid Arthritis Disease Activity Measurement and Treat‐to‐Target Outcomes. Issue 3 (11th February 2021) - Bajaj, Puneet; Kollipara, Usha; Koganti, Rama; Wang, Dan (Claire); Chennu, Navreet; Bhat, Deepa; Mutz, Jacqueline; Willett, Duwayne; Fish, Jason; Karp, David
Abstract : Objective: Rheumatoid arthritis (RA) disease activity assessment is critical for treatment decisions and treat to target (T2T) outcomes. Utilization of the electronic medical record (EMR) and techniques to improve the routine capture of disease activity measures in clinical practice are not well described. We leveraged a Lean Six Sigma (LSS) approach, a data‐driven five‐step process improvement and problem‐solving methodology, coupled with EMR modifications to evaluate improvement in disease activity documentation and patient outcomes. Methods: A RA registry was established, and structured fields for Routine Assessment of Patient Index Data (RAPID3) and Clinical Disease Activity Index (CDAI) were built in the EMR, along with a dashboard to display provider performance rates. An initial rapid‐cycle improvement intervention was launched, and subsequent LSS improvement cycles helped in standardization of clinic workflow, modifying provider behaviors, and motivating better documentation practices. Trends related to CDAI score categories were compared over time using run charts. Results: Our project included 1322 patients with RA and 10 241 encounters between April 2016 and December 2019. Initially, RAPID3 completion rates increased from 16% to 50%, and CDAI from 15% to 44% from the RCI intervention. Post LSS intervention, the RAPID3 rate increased to more than 90% (sustained at 85%), and CDAI rate increased to more than 80% (sustained at 72%). The patients in the low disease/remission category increased from 54% to 66% ( p < 0.001), and those in the high disease category decreased from 15% to 7% ( p < 0.001), demonstrating improved T2T outcomes. Conclusion: Combining EMR modifications with systems redesign utilizing LSS approach led to impressive and sustained improvement in disease activity documentation and T2T outcomes.